SPI1 Mediates N-Myristoyltransferase 1 to Advance Gastric Cancer Progression via PI3K/AKT/mTOR Pathway - Ping Qiu; Xing Li; Min Gong; Ping Wen; Jianbo Wen; Linfang Xu; Guiliang Wang (Canadian Journal of Gastroenterology and Hepatology)
Gastric cancer (GC) is a common digestive tract malignancy worldwide. N-myristoyltransferase 1 (NMT1) has been implicated in many cancers, but its association with gastric cancer remains to be clarified. Thus, this paper elucidated the role of NMT1 in GC. The NMT1 expression level in GC and normal tissue samples as well as the relationship between NMT1 high or low expression and overall survival in GC was analyzed via GEPIA. GC cells were transfected with NMT1 or SPI1 overexpression plasmid and short hairpin RNA against NMT1 (shNMT1) or shSPI1. NMT1, SPI1, p-PI3K, PI3K, p-AKT, AKT, p-mTOR, and mTOR levels were detected through qRT-PCR and western blot. MTT, wound healing, and transwell assays were applied to test cell viability, migration, and invasion. The binding relationship of SPI1 and NMT1 was determined through a dual-luciferase reporter assay and chromatin immunoprecipitation. NMT1 was upregulated in GC, the high level of which connected with a poor prognosis. Overexpressed NMT1 elevated viability, migration rate, and invasion rate of GC cells, whereas NMT1 knockdown leads to the opposite results. Besides, SPI1 could bind to NMT1. Overexpressed NMT1 reversed the effects of shSPI1 on decreasing viability, migration, invasion, p-PI3K/PI3K, p-AKT/AKT, and p-mTOR/mTOR in GC cells, and NMT1 knockdown reversed the effects of SPI1 overexpression on increasing viability, migration, invasion, p-PI3K/PI3K, p-AKT/AKT, and p-mTOR/mTOR. SPI1 upregulated NMT1 to facilitate the malignant behaviors of GC cells through the PI3K/AKT/mTOR pathway.